(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Fitness is an important component for humans in carrying out daily activities such as working productively and efficiently, walking, studying more enthusiastically, not being susceptible to disease, and being able to excel academically. The fitness level of teenagers is still experiencing a decline due to the impact of the pandemic. This PkM activity aims to increase teenagers’ knowledge in improving fitness. The PkM method consists of situation analysis, implementation, using the lecture method, and PkM evaluation. The results of this PkM show an increase in students’ knowledge about fitness by 93.84%. Meanwhile, based on the knowledge aspect of teenagers, there was the highest increase in the aspect of how to measure fitness levels with an increase of 113.80%, while based on the personal aspect of the questionnaire, the highest increase was found in question no. 8 regarding how to measure fitness levels with an average increase in score of 314.33%. Based on the results of this PkM, teenagers are advised to carry out regular exercise to improve fitness.